2022
DOI: 10.55303/mimb.v19i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Struktur Modal, Pertumbuhan Laba, dan Komite Audit Terhadap Kualitas Laba Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar Di BEI Tahun 2017-2020

Abstract: This study aims to determine the effect of capital structure, earnings growth, and audit committee on earnings quality in consumer goods industrial companies listed on the Indonesian stock exchange in 2017-2020. The population used in this study is the consumer goods industrial companies listed on the BEI as many as 52 companies. The sampling technique in this study used a purposive sampling technique which obtained 26 consumer goods industrial companies listed on the IDX in 2017-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Astuti et al (2022), earnings growth is when a company experiences an increase in earnings indicated by a percentage. Earnings growth is closely related to earnings quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Astuti et al (2022), earnings growth is when a company experiences an increase in earnings indicated by a percentage. Earnings growth is closely related to earnings quality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the influence of earnings growth on earnings quality has been conducted, but the results need to be more consistent. According to Astuti et al (2022) and Sumertiasih and Yasa (2022), earnings growth significantly and positively influences earnings quality. However, according to Rahmawati and Aprilia (2022), and Benarda and Desmita (2022), earnings growth does not impact earnings quality.…”
Section: Introductionmentioning
confidence: 99%